Hermeneutika Friedrich D.E. Schleiermacher sebagai Metode Tafsir Al-Qur’an (Kajian ayat ikhlāṣ; jilbāb; sayyārah; dan al-hudā) - Shafwatul Bary; Zakirman Zakirman (Qur'an and Hadith Academic Society, 2020)
Text, reader, and author are three entities that are interlocked in a process of understanding text. For Friedrich D.E. Schleiermacher, someone can only understand the text he/she reads if he/she delves into the author's psychological experience and knows exactly the phrases that the author uses in writing text. Talking about reading the Qur’an as a text found by modern humans today which its existence as a text is revealed in the seventh century in the Arabic nation, it is a must for anyone to know the Arabic grammatical used by the Qur'an. This article discusses linkages between the language analysis formulated by Schleiermacher and the method of understanding the Qur'an which is today found in the text form with special reference to the four key terms discussed. Using the descriptive-analysis method this research finds that Schleiermacher’s hermeneutic becomes relevant to Quranic studies because it can enrich existing interpretive methods. The concept of psychological hermeneutics will contribute to the realm of asbāb al-nuzūl study and the necessity of proper faith. Whereas the grammatical will contribute to the realm of understanding Qur’an as ancient Arabic text.